The President's daughter : a thriller - Clinton, Bill, 1946-; Patterson, James, 1947- (New York : Little, Brown and Company, Alfred A. Knopf, 2021)
Matthew Keating, a one-time Navy SEAL--and a past president--has always defended his family as staunchly as he has his country. Now those defenses are under attack. A madman abducts Keating's teenage daughter, Melanie--turning every parent's deepest fear into a matter of national security. As the world watches in real time, Keating embarks on a one-man special-ops mission that tests his strengths: as a leader, a warrior, and a father.
Keywords: Ex-presidents -- United States -- Fiction; Daughters -- Fiction; Kidnapping -- Fiction; Assassins -- Fiction; Thrillers (Fiction); Political fiction